Developing decision-making serious games using Ren’Py visual novel engine - Hafizalshah, Muhammad Hariz; Ghazali, Aimi Shazwani; Sidek, Shahrul Na’im (Institute of Advanced Engineering and Science, 2024)
Serious games are effective tools defined as games designed with a focus on explicit utility rather than the generally construed notion of games purely as a source of entertainment. Decision-making games are a type of serious game that can be developed with the intent of studying behavior, educating, appraising or other similar applications that benefit through the information collected from the decision-making process. Digital versions of serious games are gaining prominence due to a higher level of interactivity and complexity, especially in Human-Agent Interaction (HAI) applications. The development of digital serious games generally extends beyond software developers, typically involving individuals from diverse backgrounds who may not possess the necessary programming skills required for the development process. The paper proposed the use of Ren’Py, an open-source visual novel game engine as a platform to develop decision-making games. The study examined the Ren'Py game engine’s potential through an assessment of the development process for the production of a decision-making serious game. Findings showed that Ren’Py satisfies the need for a relatively easy-to-develop platform for decision-making-based serious games due to its built-in systems that conform to currently applied serious decision-making game design principles.